Application of Archimedean copula in the non-isothermal nth order distributed activation energy model. Issue 2 (4th March 2019) - Dhaundiyal, Alok; Singh, Suraj B.; Hanon, Muammel M.
ABSTRACT: The aim of this paper is to implement one of the Archimedean copulas, Gumbel–Hougaard, to determine the influence of some of the important parameters of biomass pyrolysis on the numerical solution of the n th order distributed activation energy model. The initial distribution function of activation energy is replaced by the bivariate distribution function. In this manner, the cumulative effect of different univariate functions on modelling of biomass pyrolysis can be studied. The single marginal distribution function does not exhibit flexibility in its pattern, therefore the concept of copula is introduced to analysis the pyrolysis problem qualitatively. Activation energies E 1 and E 2 are assumed to initiate the primary and the secondary pyrolysis reactions respectively. Temperature distribution is considered to vary linearly with time. Thermo-analytical data is experimentally retrieved with the help of thermogravimetry and differential thermogravimetry (TG/DTG).